The Advanced Role of Carbon Quantum Dots in Nano-Food Science: Applications, Bibliographic Analysis, Safety Concerns, and Perspectives - Abdul Majid; Khurshid Ahmad; Liju Tan; Waqas Niaz; Wang Na; Li Huiru; Jiangtao Wang (C)
Carbon quantum dots (CQDs) are innovative carbon-based nanomaterials that can be synthesized from organic and inorganic sources using two approaches: “top-down” (laser ablation, arc discharge, electrochemical, and acidic oxidation) and “bottom-up” (hydrothermal, ultrasound-assisted, microwave, and thermal decomposition). Among these, hydrothermal synthesis stands out as the best option as it is affordable and eco-friendly and can produce a high quantum yield. Due to their exceptional physical and chemical properties, CQDs are highly promising materials for diverse applications, i.e., medicine, bioimaging, and especially in food safety, which is one of the thriving fields of recent research worldwide. As an innovative sensing tool, CQDs with different surface functional groups enable them to detect food contaminants, i.e., food additives in processed food, drug residues in honey, and mycotoxins in beer and flour, based on different sensing mechanisms (IFE, PET, and FRET). This article discussed the sources, fabrication methods, advantages, and limitations of CQDs as a sensing for the detection of food contaminants. In addition, the cost-effectiveness, eco-friendliness, high quantum yield, safety concerns, and future research perspectives to enhance food quality and security were briefly highlighted. This review also explored recent advancements in CQD applications in food safety, supported by a bibliometric analysis (2014–2024) using the PubMed database.